Lipid peroxidation and paraoxonase activity in nocturnal cyclic and sustained intermittent hypoxia - YÜKSEL, MERAL (SPRINGER HEIDELBERG, 2013)
Obstructive sleep apnea (OSA) and chronic obstructive pulmonary disease (COPD) have been known to be associated with atherosclerosis and hypoxia which was suggested to have an important role in this process by the way of increased oxidative stress. In the present study, we aimed to evaluate the effects of nocturnal hypoxia pattern (intermittent versus sustained) on serum lipid peroxidation and paraoxonase (PON) activity. Blood collections were performed in 44 OSA, 11 non-apneic, nocturnal desaturated COPD, and 14 simple snorer patients after full-night polysomnographic recordings. Nocturnal sleep and respiratory parameters, oxygen desaturation indexes, serum malondialdehyde (MDA) levels by measuring with the help of the formation of thiobarbituric acid reactive substances (TBARS), and PON activity were assessed in all subjects. OSA and COPD patients showed nocturnal hypoxemia, with a minimum oxygen saturation (SaO(2)) in ranges of 53-92 % and 50-87 %, respectively. The mean levels of TBARS was 15.7 +/- 3.6 nmol and 15.3 +/- 3.4 nmol malondialdehyde (MDA)/ml in OSA and COPD patients, respectively, while the mean level of the control group was 4.1 +/- 1.2 nmol MDA/ml. The mean PON activity was found to be 124.2 +/- 35.5 U/l in OSA patients and 124.6 +/- 28.4 U/l in COPD patients. The mean PON activity of the control group was 269.0 +/- 135.8 U/l. The increase in TBARS levels and the decrease in PON1 levels were statistically significant in both OSA and COPD patients according to controls (p < 0.001 for TBARS as well as PON1). The results of this study revealed that both OSA and non-apneic, nocturnal desaturated COPD patients showed increased levels of lipid peroxidation and decreased PON activity despite the differences in nocturnal hypoxia pattern.
Keywords: Intermittent hypoxia; Obstructive sleep apnea; Chronic obstructive pulmonary disease; Paraoxonase; Lipid peroxidation; Oxidative stress; OBSTRUCTIVE SLEEP-APNEA; LOW-DENSITY-LIPOPROTEIN; 60 MM HG; PULMONARY-DISEASE; OXIDATIVE STRESS; LUNG-FUNCTION; ATHEROSCLEROSIS; ASSOCIATION; ACTIVATION; MORTALITY